Nonlinearity in MCF7 Cell Survival Following Exposure to Modulated 6 MV Radiation Fields: Focus on the Dose Gradient Zone. Issue 4 (28th October 2015) - Lacoste-Collin, Laetitia; Castiella, Marion; Franceries, Xavier; Cassol, Emmanuelle; Vieillevigne, Laure; Pereda, Veronica; Bardies, Manuel; Courtade-Saïdi, Monique
The study of cell survival following exposure to nonuniform radiation fields is taking on particular interest because of the increasing evidence of a nonlinear relationship at low doses. We conducted in vitro experiments using the MCF7 breast cancer cell line. A 2.4 × 2.4 cm 2 square area of a T25 flask was irradiated by a Varian Novalis accelerator delivering 6 MV photons. Cell survival inside the irradiation field, in the dose gradient zone and in the peripheral zone, was determined using a clonogenic assay for different radiation doses at the isocenter. Increased cell survival was observed inside the irradiation area for doses of 2, 10, and 20 Gy when nonirradiated cells were present at the periphery, while the cells at the periphery showed decreased survival compared to controls. Increased survival was also observed at the edge of the dose gradient zone for cells receiving 0.02 to 0.01 Gy when compared with cells at the periphery of the same flask, whatever the isocenter dose. These data are the first to report cell survival in the dose gradient zone. Radiotherapists must be aware of this nonlinearity in dose response.